Análisis y desarrollo de la aplicación móvil Mouse y teclado remoto para compartir con estudiantes la pc del aula, para la carrera de ingeniería de sistemas de la universidad Politécnica Salesiana. - Carrillo Tomala, Xavier (2018)
The application to be developed, the functionality features of the other existing applications available to the student and the learning experience of the students, as well as the teaching of learning